Targeted Drug Delivery via the Use of ECM-Mimetic Materials - Hwang, Jeongmin; Sullivan, Millicent O.; Kiick, Kristi L. (Frontiers in Bioengineering and Biotechnology, 2020)
The use of drug delivery vehicles to improve the efficacy of drugs and to target their action at effective concentrations over desired periods of time has been an active topic of research and clinical investigation for decades. Both synthetic and natural drug delivery materials have facilitated locally-controlled as well as targeted drug delivery. Extracellular matrix (ECM) molecules have generated widespread interest as drug delivery materials owing to the various biological functions of ECM. Hydrogels created using ECM molecules can provide not only biochemical and structural support to cells, but also spatial and temporal control over the release of therapeutic agents, including small molecules, biomacromolecules, and cells. In addition, the modification of drug delivery carriers with ECM fragments used as cell-binding ligands has facilitated cell-targeted delivery and improved the therapeutic efficiency of drugs through interaction with highly-expressed cellular receptors for ECM. The combination of ECM-derived hydrogels and ECM-derived ligand approaches shows synergistic effects, leading to a great promise for the delivery of intracellular drugs, which require specific endocytic pathways for maximal effectiveness. In this review, we provide an overview of cellular receptors that interact with ECM molecules and discuss examples of selected ECM components that have been applied for drug delivery in both local and systemic platforms. Finally, we highlight the potential impacts of utilizing the interaction between ECM components and cellular receptors for intracellular delivery, particularly in tissue regeneration applications.